PENGGUNAAN MEDIAGAMBAR UNTUK MENINGKATKAN KEMAMPUANMENGUASAI KALIMAT PREDIKAT KATA KERJA â€œSHI...DEâ€ PADASISWA SMP - Julianti, Melly; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractGrammar is one of the main contents of language teaching. The same is true of chinese. One of the main words of chinese grammar is the verb predicate statement â€œ Shiâ€¦Deâ€. The verb predicate statement â€œShiâ€¦Deâ€ is a difficult problem in chinese grammar,especially junior high school students. Most students donâ€™t know how to use verb to predicate statement â€œShiâ€¦Deâ€ usage. In order to help students more easily grasp the verb predicate statement â€œShiâ€¦Deâ€ usage,the author did experiment. First of all,the author of LKIA second-year students carried out a pre-test,and then the use of picture teaching aids for the three hours verb predicate statement â€œShiâ€¦Deâ€ teaching. Through the post-test, the author found that the use of picture teaching helped students to improve their ability on the verb predicate statement â€œShiâ€¦Deâ€.Â Keywords: grammar, picture teaching aids, predicate statement â€œShiâ€¦Deâ€